(untitled) (Eurasian Journal of Ecology, 2024)
This article is dedicated to studying the complex ecology of the Volga-Ural saiga population in Kazakhstan, providing comprehensive information about its current state and dynamics. Extensive field studies were conducted in key locations such as calving sites, summer pastures, and wintering grounds to understand habitat conditions, ecological characteristics, and relationships with other animal species. The increasing population of Volga-Ural saigas has led to conflicts of interest with agricultural producers, which have been examined alongside proposed measures for resolution. Currently, this population is the world`s largest, uniquely positioned in the border area between Kazakhstan and the Russian Federation. In recent years, saigas have been observed crossing the borders of these countries in the west and northwest of the West Kazakhstan region during spring, seeking calving sites. Fluctuation in saiga numbers from perilous lows to record highs within several years, raise concerns about sustainable long-term development. The author`s research seeks to address these questions and aligns with other researchers advocating for population regulation through controlled reduction necessary to manage the rapidly increasing saiga population effectively. Furthermore, this article serves as a valuable resource for conservation stakeholders, including those interested in saiga protection and regional agriculture development. It significantly contributes to understanding the intricate ecosystem dynamics along the right bank of the Ural River, emphasizing the importance of sustainable natural resource management for saiga conservation and overall biodiversity in the region. Key words: saiga, population, epizootic, migration, habitat, predators